A Functionally Different Immune Phenotype in Cattle Is Associated With Higher Mastitis Incidence - Lutterberg, Karina; Kleinwort, Kristina J. H.; Hobmaier, Bernhard F.; Hauck, Stefanie M.; Nüske, Stefan; Scholz, Armin M.; Deeg, Cornelia A. (Frontiers in Immunology, 2018)
A novel vaccine against bovine viral diarrhea (BVD) induced pathogenic antibody production in 5-10% of BVD-vaccinated cows. Transfer of these antibodies via colostrum caused Bovine neonatal pancytopenia (BNP) in calves, with a lethality rate of 90%. The exact immunological mechanisms behind the onset of BNP are not fully understood to date. To gain further insight into these mechanisms, we analyzed the immune proteome from alloreactive antibody producers (BNP cows) and non-responders. After in vitro stimulation of peripheral blood derived lymphocytes, we detected distinctly deviant expression levels of several master regulators of immune responses in BNP cells, pointing to a changed immune phenotype with severe dysregulation of immune response in BNP cows. Interestingly, we also found this response pattern in 22% of non-BVD-vaccinated cows, indicating a genetic predisposition of this immune deviant (ID) phenotype in cattle. We additionally analyzed the functional correlation of the ID phenotype with ten health parameters and six diseases in a retrospective study over 38 months. The significantly increased prevalence of mastitis among ID cows emphasizes the clinical relevance of this deviant immune response and its potential impact on the ability to fight infections.